Pengaruh Kurikulum dan Iklim Pesantren terhadap Akhlak Santri pada Pondok Pesantren DDI Kaballangang - Saparuddin Saparuddin; Muh. Ilyas Ismail (Madrasah Tsanawiyah DDI Cilellang, 2022)
The purpose of this study was to analyze the influence of the curriculum and the climate of Islamic boarding school on the morals of students in DDI Kaballangang Islamic Boarding School, Pinrang Regency both partially and simultaneously. This type of research is a survey with a quantitative approach. Data collection methods using questionnaires, documentation, and observation. Data analysis using descriptive statistical analysis techniques and inferential statistical analysis techniques. The results showed that the curriculum and climate of the Islamic boarding school had a positive and significant effect both partially and simultaneously on the morals of the students in DDI Kaballangang Islamic Boarding School, Pinrang Regency. Based on the calculation of the coefficient of determination obtained the R Square of 0.014, which means that the curriculum and the climate of Islamic boarding school simultaneously influence 14.0% on the students' morals, while the remaining 86.0% is influenced by other factors not examined in this research.